POST-GRADUATION STUDENTS' ATTITUDE AND PERCEPTION TOWARDS USE OF SMARTPHONES FOR HIGHER LEARNING WITH REFERENCE TO CHITTOOR DISTRICT, ANDHRA PRADES, INDIA. - Dr.B.Sankar Naik, Dr. M.Venkat Ramana, Dr. A.K Neeraja Rani (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Purpose The intention of this research article is to rapid growth in technology and the advancement in education system, Acknowledgment of smartphones by students in higher education has been a universal experience in modern days. The main objective of this research paper is to comprehend and evaluate students' attitudes and perceptions towards the effectiveness of smart phones for higher learning with reference to Chittoor District, Andhra Pradesh, India. Design/methodology/approach Descriptive research method is used for this study employing quantitative approaches. A prepared well structured opinion poll was used to accumulate the data through investigation method and convenience sampling was adopted. A total of 150 questionnaires with self explanatory questions were administered to students of selected institutions in Chittoor District and out of which 120 were returned. MS-Excel and also the SPSS Package were used for coding the data. Data will be analyzed using a variety of statistical instruments. Findings The results clearly indicate that a very positive attitude towards higher learning. However, this study highlights that there is no association between smart phone usage and gender among the post-graduation student. Practical implications The consequences of this investigate paper have realistic implication for higher learning prog rammes' policymakers, educators and developers, exclusively for developing countries. Secon d implication, the results are based on selfreported responses from postgraduate students from only three disciplines. Originality/value The paper links smartphone use for learning activities to educational services valuecreation processes. The discussion presented here makes it the main focus and argues that for educational purposes, most respondents see smartphones as an important medium.